Femoral nonunion with segmental bone defect treated by distraction osteogenesis with monolateral external fixation. Issue 1 (December 2017) - Zhang, Qun; Zhang, Wei; Zhang, Zhuo; Zhang, Licheng; Chen, Hua; Hao, Ming; Deng, Junhao; Tang, Peifu
Abstract Background Currently, the common treatment for femoral nonunion with large segmental bone defect is difficult and complex. The effective surgical methods are rare, include vascularized bone grafting, Masquelet technique and Ilizarov distraction osteogenesis. The objective of this study is to investigate the outcomes of segmental femoral defects treated with monolateral external fixation using the distraction osteogenesis. Methods We retrospectively analyzed patients with femoral nonunion with segmental bone defects (> 6 cm) between January 2010 and January 2014 in our single trauma center. All patients were treated by distraction osteogenesis with monolateral external fixation. All surgeries were performed by the same surgeon. Bone union, duration of distraction osteogenesis in days, time to consolidation in months, external fixation index (EFI), complications, and additional surgical interventions were recorded postoperatively. The modified Application of Methods of Illizarov (ASAMI) criteria were used to evaluate the operative effectiveness. Results Forty-one patients were enrolled in this study for analysis. The length of the bone defect ranged from 6 to 17 cm. All patients eventually achieved healing, and no patient experienced recurrence of infection or newly developed infection. The average time needed for healing was 13 months. In terms of the incidence of complications, 3 cases axial deviations, 5 cases docking site nonunion, 23 cases pin-tract infection, 14 cases knee joint stiffness or their joint mobility declined, 2 cases osteogenesis insufficient in the distraction area, 1 case refracture, and 2 cases loose external fixation pins. In terms of the evaluations of fracture healing and function, 30 patients excellent, 6 patients good, 5 patients fair, and 0 patient poor. In terms of postoperative function evaluations, 21 patients excellent, 9 patients good, 7 patients fair, and 4 patients poor. Conclusion For patients with femoral nonunion with large segmental bone defects, the monolateral external fixation can provide effective stability, improve compliance, and reduce complications.